2007
DOI: 10.1016/j.physletb.2007.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Neutral minima in two-Higgs doublet models

Abstract: We study the neutral minima of two-Higgs doublet models, showing that these potentials can have at least two such minima with different depths. We analyse the phenomenology of these minima for the several types of two-Higgs doublet potentials, where CP is explicitly broken, spontaneously broken or preserved. We discover that it is possible to have a neutral minimum in these potentials where the masses of the known particles have their standard values, with another deeper minimum where those same particles acqu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 33 publications
0
105
1
Order By: Relevance
“…However, in addition to the minima we find in the way depicted above, there might be other minima with a lower value of the potential [54] and a better algorithm would be advisable which is beyond the scope of this work.…”
Section: Parameter Scan Methodsmentioning
confidence: 90%
“…However, in addition to the minima we find in the way depicted above, there might be other minima with a lower value of the potential [54] and a better algorithm would be advisable which is beyond the scope of this work.…”
Section: Parameter Scan Methodsmentioning
confidence: 90%
“…Another feature that a more involved scalar potential encompasses is the possibility of different symmetry breaking patterns and the 2HDM is no exception [34][35][36][37][38][39][40]. With additional Higgs doublets, this complexity increases substantially [41][42][43][44].…”
Section: Jhep11(2017)106mentioning
confidence: 99%
“…While positivity may be satisfied for the given parameters of the potential, the considered minimum need not be the global one. However, it has been shown that, if a local charge-conserving minimum exists, then there can be no charge-breaking minimum [40][41][42]. Nevertheless, the potential of the 2HDM can have more than one charge-conserving minimum.…”
Section: Theoretical Constraintsmentioning
confidence: 99%